2005
DOI: 10.1523/jneurosci.0847-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization and Neuronal Modeling of the Effects of Childhood Absence Epilepsy Variants ofCACNA1H, a T-Type Calcium Channel

Abstract: Sequencing of the T-type Ca2ϩ channel gene CACNA1H revealed 12 nonsynonymous single nucleotide polymorphisms (SNPs) that were found only in childhood absence epilepsy (CAE) patients. One SNP, G773D, was found in two patients. The present study reports the finding of a third patient with this SNP, as well as analysis of their parents. Because of the role of T-channels in determining the intrinsic firing patterns of neurons involved in absence seizures, it was suggested that these SNPs might alter channel functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(147 citation statements)
references
References 61 publications
8
137
0
2
Order By: Relevance
“…Twin studies have also suggested a strong genetic basis for the complex epilepsies (Berkovic et al, 1998); however, description and validation of the underlying genetic variation for these more common epilepsies has only just begun. Changes in channel properties of CACNA1H are consistent with complex epilepsy (Khosravani et al, 2004(Khosravani et al, , 2005Vitko et al, 2005). The present study reinforces and extends the previously reported role of GABRD as another susceptibility gene underlying complex epilepsy.…”
Section: Implication Of Gabrd In Complex Epilepsiessupporting
confidence: 91%
“…Twin studies have also suggested a strong genetic basis for the complex epilepsies (Berkovic et al, 1998); however, description and validation of the underlying genetic variation for these more common epilepsies has only just begun. Changes in channel properties of CACNA1H are consistent with complex epilepsy (Khosravani et al, 2004(Khosravani et al, , 2005Vitko et al, 2005). The present study reinforces and extends the previously reported role of GABRD as another susceptibility gene underlying complex epilepsy.…”
Section: Implication Of Gabrd In Complex Epilepsiessupporting
confidence: 91%
“…Notably, deletion of multiple regions produced nearly (100% in A). The various CAE SNPs are presented as by Vitko et al (2005). One construct harboring two SNPs, G773D and R788C (Chen et al, 2003b;Vitko et al, 2005), is labeled Double.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, these results define two roles for this intracellular loop: (1) as an intracellular gating factor that controls the voltage dependence of channel gating and (2) as a regulator of channel surface expression. Previous studies have shown that the polymorphisms associated with CAE are capable of altering channel function (Khosravani et al, 2004;Vitko et al, 2005). The effects of the polymorphisms were modest, and the only common finding was that they led to an increase in persistent currents.…”
Section: Discussionmentioning
confidence: 99%
“…85,86 Functional expression studies with several of these mutations have revealed a gain of function. 87,88 At least 30 mutations in CACNA1H, some involving splicing defects, are associated with CAE and other idiopathic generalized epilepsies. 89 Five mutations in EFHC1, a gene encoding a protein with an EF-hand motif, have been found in families with juvenile myoclonic epilepsy (JME).…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%